Case Review: Uji Absorpsi-Elusi Bercak Darah pada Barang Bukti dari Kasus Berbeda yang Ada di Bidang Laboratorium Forensik Polda Jawa Timur - istiana firqah abid (Universitas Udayana, 2025)
In the investigation process, identifying spots that are suspected to be blood is very important to support the investigation. Blood identification results can be used as a guide to determine the identity of the victim, perpetrator and even the identity of the missing person. Therefore, the blood group identification method used is the elution-absorption test. This test is used to examine evidence in the form of plastic bags, plumbing keys, machetes and their sheaths in cases with different victims. The results of the examination showed that the evidence in the form of plastic bags and plumbing keys had blood type A and the machete and its scabbard had blood type O. The results obtained were in accordance with the victim's blood type.